3D Printed Neural Regeneration Devices. (8th November 2019) - Joung, Daeha; Lavoie, Nicolas S.; Guo, Shuang‐Zhuang; Park, Sung Hyun; Parr, Ann M.; McAlpine, Michael C.
Abstract: Neural regeneration devices interface with the nervous system and can provide flexibility in material choice, implantation without the need for additional surgeries, and the ability to serve as guides augmented with physical, biological (e.g., cellular), and biochemical functionalities. Given the complexity and challenges associated with neural regeneration, a 3D printing approach to the design and manufacturing of neural devices can provide next‐generation opportunities for advanced neural regeneration via the production of anatomically accurate geometries, spatial distributions of cellular components, and incorporation of therapeutic biomolecules. A 3D printing‐based approach offers compatibility with 3D scanning, computer modeling, choice of input material, and increasing control over hierarchical integration. Therefore, a 3D printed implantable platform can ultimately be used to prepare novel biomimetic scaffolds and model complex tissue architectures for clinical implants in order to treat neurological diseases and injuries. Further, the flexibility and specificity offered by 3D printed in vitro platforms have the potential to be a significant foundational breakthrough with broad research implications in cell signaling and drug screening for personalized healthcare. This progress report examines recent advances in 3D printing strategies for neural regeneration as well as insight into how these approaches can be improved in future studies. Abstract : 3D printed platforms that combine cells, biomolecules, and scaffolds are growing in promise for combinatorial strategies in neural regeneration. This progress report focuses on the application of various 3D printing approaches to neuronal regeneration devices and mimicking the nervous system on a chip. Current challenges and future opportunities are highlighted to develop clinical implants to treat neurological diseases and injuries.